Measuring Resilience of a Tourism Village Against Flash Flood Disaster - Usman, Fadly; Hariyani, Septiana; Kurniawan, Eddi Basuki; Sari, Indah Cahayaning (Perencanaan Wilayah dan Kota FT UB, 2023)
One of the most popular tourist destinations in East Java is Batu City, which had been visited by 2.4 million tourists in 2021 during the pandemic, regardless of the fact that 7.2 million tourists normally have visited the city annually before the outbreak. Flash floods that struck Batu City in November 2021 resulted in significant damage and losses which affected several tourism villages. The preparedness of Batu City for potential natural catastrophes was identified throughout this study. It is essential to think of both technological and non-technical ways as preventive measures before a tragedy arises, given how eager travelers are to visit Batu City. Several city-scale analyses are conducted, notably by doing spatial analysis with the use of GIS technology in order to understand land use and probable flow routes. A livelihood asset analysis was used as a methodological and indicator assessment of disaster preparedness in one of the Resilient Village (Destana). The findings indicate that land conversion in production and protected forest areas change into agricultural areas is one factor that triggers flash floods. After a ten-year decline, only 20% of the forest stands are left in hilly and steep terrain, with the rest being farmland and human settlements. Meanwhile, an assessment of the community preparedness in the Tourism Village reveals that the community has a strong capability in terms of financial, social, and natural capital.